The Nutritional Value of Sorghum bicolor Stem Flour Used for Infusion Drinks in Nigeria (Biological Sciences - PJSIR, 2006)
The black purple sheath (stem) of Sorgum bicolor, used locally as colour additive in cooked meals and infusion drinks taken as beverages, was examined for its nutritive value. The stem made into flour, was found to be rich in energy (1121.3 kJ/100 g), and in some micronutrients (mg/100 g), such as Mg (185.33), Ca (151.70), K (138.87), Na (127.61), and Fe (10.98). High Mg content of stem may be useful for overcoming Mg deficiency. The Fe content was sufficient to meet the daily-required intake (DRI) value for human beings. The presence of Cu, Zn and Mn was also observed. The content of crude fibre (32.0%) and carbohydrates (44.50%) were useful for making the stem a fodder for animal con- sumption. However, the protein content of the stem was low (3.20%). The functional properties observed for the stem compared favourably with those already reported for some other plants such as pigeon pea flour, African yam bean, and wheat flour.